(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The role of neologisms as an effective means of advertisement texts expressiveness has been identified; activity of neolexemes on a morphological sign was elucidated and the methods of the new words formation have been analyzed.